2021
DOI: 10.21608/edj.2021.51346.1366
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation Of The Efficiency of Intralesional Injection Of Autologous Platelet Rich Plasma In Treatment Of Erosive Oral Lichen planus.

Abstract: Oral lichen planus (OLP) could be a doubtless malignant autoimmune disease, characterized by burning and pain that reduces the standard of patient's life. Treatment of OLP remains a significant challenge despite the recent advances in understanding the immunopathogenesis.The properties of Platelet-rich plasma suggested its application in clinical practice for treatment of OLP patients that do not respond to conventional therapy. This study aims to evaluate the effectiveness of intralesional Platelet rich Plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Furthermore, the Hijazi study [ 20 ] suggested that although PRP had a slower clinical response than TA injections, both treatments exhibited similar complete remission rates, with no significant differences observed in pain score, Sign score, or lesion area remission. The observed differences could be attributed to variations in the duration of release and peak time of GFs reported across studies [ 36 , 37 ].The UE Shinnawi study [ 38 ] also supports this notion, showing a clear improvement in symptoms with blood derivatives after the first two weeks of treatment. Several other studies have assessed the efficacy of injection PCs in managing refractory erosive OLP patients who showed no response to corticosteroid treatment [ 39 ].…”
Section: Discussionmentioning
confidence: 76%
“…Furthermore, the Hijazi study [ 20 ] suggested that although PRP had a slower clinical response than TA injections, both treatments exhibited similar complete remission rates, with no significant differences observed in pain score, Sign score, or lesion area remission. The observed differences could be attributed to variations in the duration of release and peak time of GFs reported across studies [ 36 , 37 ].The UE Shinnawi study [ 38 ] also supports this notion, showing a clear improvement in symptoms with blood derivatives after the first two weeks of treatment. Several other studies have assessed the efficacy of injection PCs in managing refractory erosive OLP patients who showed no response to corticosteroid treatment [ 39 ].…”
Section: Discussionmentioning
confidence: 76%
“… 36 Likewise, intralesional PRP injections in cases with recalcitrant erosive OLP for 4–8 weeks showed a significant reduction in pain, ulcer size, and erythema. 37 , 38 , 39 , 40 , 41 In addition, a randomized clinical trial showed that PRF injections in OLP resulted in a significant reduction of lesion size, pain score, and decreased mean values of oral health impact profile scale, which were comparable to corticosteroid injections. 42 , 43 , 44 Overall, clinical studies suggest that applying PCs either topically or intralesional for an average of eight weeks would be a valid treatment option for recalcitrant OLP lesions.…”
Section: Clinical Application Of Pc In Chronic Oral Mucosal Diseasesmentioning
confidence: 99%
“… Lesion Type of PCs Effect of PCs Ref. Oral lichen planus PRF membrane PRF resulted in a decrease in lesions' size within 3 weeks of treatment 36 Platelet solution PC improved quality of life and decreased pain 35 PRP Complete regression of the lesion after 4 weeks 41 PRP 90% of patients reported complete resolution of erythema 40 PRP Significant reduction in pain, size of the lesion and inflammation 37 i-PRF i-PRF reduced the lesion size by 59.8% and reduced the VAS scores by 47.6% 65 i-PRF i-PRF reduced pain and lesion's size 44 PRP PRP reduced pain and size of the ulcers 39 i-PRF i-PRF reduced VAS scores and lesion size by 68.5% and 74%, respectively 42 PRP Significant decrease in lesion size and pain score 38 Oral mucositis Platelet lysate Healing was good-to-complete in 5 out of 7 cases 50 Platelet gel Platelet gel resulted in improvement of oral mucosa, revealing restitutio ad integrum 46 Platelet gel PC resulted in improved quality of life and pa...…”
Section: Clinical Application Of Pc In Chronic Oral Mucosal Diseasesmentioning
confidence: 99%